Causal Estimates of the Intangible Costs of Violence against Women in Latin America and the Caribbean - Jorge Aguero (Inter-American Development Bank (IDB), 2013)
Violence has a striking gender pattern. Men are more likely to be attacked by a stranger, while women experience violence mostly from their partners. This paper estimates the costs of violence against women in terms of intangible outcomes, such as women's reproductive health, labor supply, and the welfare of their children. The study uses a sample of nearly 83,000 women in seven countries from all income groups and all sub-regions in Latin American and the Caribbean. The sample, consisting of 26. 3 million women between the ages of 15 and 49, strengthens the external validity of the results. The results show that physical violence against women is strongly associated with their marital status because it increases the divorce or separation rate. Violence is negatively linked with women's health. The study shows that domestic violence additionally creates a negative externality by affecting important short-term health outcomes for children whose mothers suffered from violence. To obtain the child health outcomes, the study employs a natural experiment in Peru to establish that these effects appear to be causal. Finally, the paper presents evidence indicating that women's education and age buffer the negative effect of violence against women on their children's health outcomes.
Keywords: I12; I3; J16; 330